Evaluation Of The Role Of Matrix Metalloproteinases In The Pathogenesis And Course Of Acute Myocardial Infarction - SREEKANTH.K.SIVARAMAN; GEEVAR ZACHARIAH; P.T.ANNAMALA (International Journal of Pharma and Bio Sciences, 2012)
Matrix Metalloproteinases (MMPs), a class of Zn containing enzymes are involved in the erosion of the fibrous cap and rupture of the plaque which leads to Acute Myocardial Infarction (AMI). Though the exact mechanism of the involvement of MMPs in AMI is not clear, evidence suggest that they play a major role in different phases of AMI. Our aim was to evaluate the role of MMP2 and MMP9 in AMI patients, based on certain risk factors and also to study their variation in these risk groups and to identify which MMP among these two shows a significant variation when compared to the other so that it can be used as a specific marker for the diagnosis of AMI. For that the blood samples from three hundred AMI patients and hundred sex and age matched control subjects were analysed for MMP2 and MMP9 by sandwich enzyme immuno assay and the values were noted. It is found that both MMP2 and MMP9 were found to be significantly elevated in all the AMI patients irrespective of the risk factors taken into account. However MMP 9 shows a considerable elevation when compared to MMP2, which indicates its potential role in AMI, and hence can be used as a marker for the disease.